PERAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA MELALUI MOTIVASI DAN PERILAKU KEWARGAAN ORGANISASIONAL/OCB STUDI PADA BADAN PELAKSANA PENYULUHAN KABUPATEN TEMANGGUNG - Toifur Hadi Wuryanto, 11.52.02.0040 (Students Journal of Economic and Management, 2013)
This study aims to analyze the role of transformational leadership on job satisfaction with the mediation of motivation and Organizational Citizenship Behaviour (OCB) at the Agricultur Extension Board (Badan Pelaksana Penyuluh) of the Temanggung Regency in 2012. The population in this study was Â civil servant at the Agricultur Extension Board in 20 districts in of the Temanggung Regencywith the members of 110 employees. The number of data treated from respondents and there are 104 respondents. The study found that Transformational Leadership, Motivation and Organizational Citizenship Behaviour (OCB) positive effect on Job Satisfaction. Organizational Citizenship Behaviour (OCB) more influence than Transformational Leadership and motivation have in job satisfaction with the of compare and respecticaly. while the percentage of mediation effect either through motivation, Organizational Citizenship Behaviour (OCB) or with motivation and Organizational Citizenship Behaviour (OCB), respecticaly. Therefore direct influence is more substantial than the influence of mediation. Keywords: Transformational Leadership, Motivation, Organizational Citizenship Behaviour (OCB) and Job Satisfaction